Continuing professional development for sports coaches: a road less travelled. Issue 12 (2nd December 2017) - Nash, Christine; Sproule, John; Horton, Peter
Abstract: In the UK, there is currently no coherent model of professional development for coaching personnel. CPD should maintain currency of professional practice while enhancing knowledge and understanding. This study used interviews to examine coaches' views of CPD, whether they understood the key principles and to assess whether or not they value or appreciate its necessity. Three themes emerged from the interview data; the value placed on CPD, coach development and the input of the NGB/Sporting Organisation. Many coaches in this study felt that they did not value CPD, because they could not see it developing them as coaches nor did it appear to be to be a priority with their NGBs. This study suggests that any CPD model for coaching needs to move from a more prescriptive provision at the earlier stages of certification to one that is more individualized and flexible at the later stages.